Transforming Social Assistance into Sustainable Household Welfare: A Financial Literacy and Economic Empowerment Model - fahri abdullah; Samsidar; Andi Fajriansyah (CV Edujavare Publishing, 2026)
Social assistance is a central instrument of social protection policy aimed at reducing poverty and improving household welfare, yet empirical evidence shows that its effectiveness in producing sustainable welfare outcomes remains inconsistent: some households achieve lasting improvement while others remain vulnerable despite receiving aid regularly. This article aims to develop a conceptual model explaining how social assistance can be transformed into sustainable household welfare through financial literacy and economic empowerment. Using a qualitative library research approach in the form of a conceptual paper, the study synthesizes theories and prior findings from reputable scholarly journals, academic books, international institutional reports, and government policy documents, analyzed through content analysis and narrative synthesis. The results show that social assistance should not be viewed as the end goal of welfare policy, but as an initial instrument that must be integrated with financial literacy and economic empowerment. Based on this synthesis, the article proposes the Integrated Household Welfare Transformation Model (IHWTM), a conceptual model explaining the transformation process from social assistance to sustainable household welfare. The model is expected to enrich social protection theory and serve as a reference for designing more adaptive, productive, and sustainable welfare policies.